Brain functional connectivity after Stroop task induced cognitive fatigue - Jilin Wu; Zhongtian Guan; Chunlin Li; Wei Wang; Ruifeng Sun; Ziman Zhu; Li Song; Weijun Gong (Scientific Reports)
Abstract We aim to investigate the changes in brain functional connectivity induced by cognitive fatigue from a whole-brain perspective and multiple angles to uncover the underlying mechanisms in healthy individuals, thereby enhancing high-quality cognitive activities and the effectiveness of cognitive rehabilitation training. This study involved 48 healthy adults aged 20–35 and was conducted in two phases: cognitive fatigue validation and whole-brain connectivity feature analysis. We used fMRI to compare Amplitude of Low-Frequency Fluctuations (ALFF), Regional Homogeneity (ReHo), Functional Connectivity (FC), and graph theory metrics before and after cognitive fatigue. The results indicated that changes in activity within the bilateral thalamus and Front-Parietal network were significantly correlated with subjective fatigue levels. Additionally, the left precuneus, cerebellum, and certain frontal regions may contribute to the neural regulation of cognitive fatigue through various mechanisms. These findings provide a reliable theoretical basis for developing new strategies to mitigate cognitive fatigue and offer valuable insights for optimizing rehabilitation plans for patients with cognitive impairments.